2009
DOI: 10.1007/s10549-009-0495-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on serum 25-hydroxy vitamin D levels, joint pain, and fatigue in women starting adjuvant letrozole treatment for breast cancer

Abstract: Vitamin D deficiency and insufficiency may contribute to musculoskeletal symptoms and bone loss observed in women taking aromatase inhibitors (AIs). This study was conducted to determine the prevalence of suboptimal vitamin D levels in women initiating adjuvant letrozole for breast cancer and to determine whether supplementation with 50,000 IU of vitamin D3 weekly could reduce musculoskeletal symptoms and fatigue in women who have suboptimal vitamin D levels. Sixty women about to begin an adjuvant AI were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 28 publications
11
136
2
7
Order By: Relevance
“…In a previous study of women of different ethnicities starting letrozole, there was a prevalence of vitamin D deficiency of 18/60 and with only 13/60 with concentrations > 100nM [18]. In this study, which measured 25(OH)D using liquid chromatography with mass spectroscopy (LC/MS) , the threshold was approximately 165 nM (equivalent to 66 ng/ml) using disability from joint pain as the outcome.…”
Section: Ai-associated Joint Pain and Vitamin D Status At 3 Monthsmentioning
confidence: 80%
See 2 more Smart Citations
“…In a previous study of women of different ethnicities starting letrozole, there was a prevalence of vitamin D deficiency of 18/60 and with only 13/60 with concentrations > 100nM [18]. In this study, which measured 25(OH)D using liquid chromatography with mass spectroscopy (LC/MS) , the threshold was approximately 165 nM (equivalent to 66 ng/ml) using disability from joint pain as the outcome.…”
Section: Ai-associated Joint Pain and Vitamin D Status At 3 Monthsmentioning
confidence: 80%
“…The mechanism for this association is unclear, It has been proposed [18] that the AI induced reduction in estrogen may unmask subclinical osteomalacia through the loss of estrogen mediated activation of 1alpha hydroxylase [35], the vitamin D receptor [36,37] and/or vitamin D binding protein. In addition, AI use may attenuate vitamin D metabolism through competition with the hepatic CYP3A4 system [18]. Conversely, the promoter region of the aromatase gene is also activated by vitamin D in a number of tissues [38] hence higher concentrations of vitamin D may attenuate local estrogen deficiency [39].…”
Section: Ai-associated Joint Pain and Vitamin D Status At 3 Monthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, recent studies have reported that daily vitamin D supplements may have a protective effect on pathogenesis (Khan et al 2010, Rastelli et al 2011. This observation may represent a promising possibility for maintaining quality of life and for preventing discontinuation of a potentially life-saving adjuvant anticancer treatment.…”
Section: Musculoskeletal Symptomsmentioning
confidence: 99%
“…After 16 weeks of letrozole, the absence of joint disability was reported in more women with 25-OHD levels above rather than below 66 ng/ml (52 vs. 19%, P = 0.026). This suggests that there may be a role of vitamin D, although a limitation of this study was that it was not randomised and there was no placebo control [66].…”
Section: Intervention Studiesmentioning
confidence: 99%